High sensitivity C-Reactive Protein is a Significant Predictor for Hypertension and Obesity in Iraqi Postmenopausal Women - Hussein, Waleed Kh.; Al-Bayatti, Ansam A.; Salman, Esam N. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: several new inflammatory markers have emerged as strong predictors of cardiovascular disease in healthy and non-healthy subjects, one of these markers is hs-CRP, which has been proposed as independent risk factor for cardiovascular disease, and it is positively associated with body weight. Little is known, however, about the utility of hs-CRP and other biomarkers in obese hypertensive Iraqi post menopausal women.The aim of study is to examine the hypothesis that there is a relation between obesity, hypertension and a chronic low-grade inflammatory status (represented by high hs-CRP). Patients and Methods: A total number of 99 postmenopausal women classified into obese hypertensive group (case) and non obese non hypertensive group(control). For these groups, measurement of zinc, calcium, phosphorus, lipid profile, High sensitivity C–Reactive Protein, body mass index and waist circumference were done. Results: The (Mean ± SD) of hs-CRP in the cases and controls were (5.74 ± 2.1) mg/land (2.1 ± 0.8) mg/l respectively, (P < 0.001).Calcium, phosphorus, zinc and triglycerides showed no statistical significance between the groups (Pvalue >0,05) while body mass index , waist circumference ,HDL ,LDL ,and total were statistically significant (Pvalue <0,05). Conclusion: There is an elevated serum level of hs-CRP in hypertensive and obese subjects in comparison with low levels in control group (non obese non hypertensive) which suggest a role of hs- CRP in developing hypertension and obesity.